Hubungan antara jenis asupan karbohidrat dan lemak dengan kadar small dense low density lipoprotein pada pasien penyakit jantung koroner - Sofia, Sefri Noventi; Sugiri, Sugiri; Utami, Sulistiyati Bayu; Nugroho, M. Arif; Murbawani, Etisa Adi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background: small dense Low Density Lipoprotein (sdLDL) was the most atherogenic lipoprotein. Its influenced by internal and external factors including food consumption. Indonesian people mostly take a diet of high carbohydrate (CH) and fried food that believed to correlate with higher sdLDL level and predisposed to Coronary Heart Disease (CHD). There were 2 types of CH based on the processing ways, refined and non-refined CH.Objectives: The study’s purpose was to prove the correlation between different types of CH and fat intake with the sdlDL level in CHD patients.Methods: cross sectional in CHD patients hospitalized at Dr Kariadi hospital. The sdLDL and others lipid profile examined. The type and amount of CH and fat intakes per-day were collect from an interview using semi-quantitative food frequency questionnaire (SQFFQ) and food models. Pearson and Spearman test used for bivariate analysis. Confounding factors age, gender, physical activity, diabetes mellitus and smoking were analyzed. Variables with p<0,25 was included in multivariate analysis using linear regression test.Results: There were 30 samples with CHD came with acute coronary syndrome (ACS). Mean of total CH intake per day was 267.75 gram. Mean of percentage of CH from total calories per day was 55.93%. This number was higher than advised which is 30-130 gram or <45% of total calorie per day. Mean of refined and non-refined CH intake was 161.80 and 57.81 gr/day. The total CH mostly from refined CH (76%) rather than non-refined. Mean of fat intake was 68 gr/day (32.76% of total energy per day), and the mean of sdLDL level was 26,54 mg/dl. Correlation between refined CH vs non-refined CH with the sdLDL levels (r=0.328; p=0.077 vs r=-0.184;p=0.331). Correlation between fat intake and sdLDL levels (r=0.44;p=0.15). Multivariate analysis was analyzing refined CH fat intake and age with sdLDL level (r=0,28;p=0,13 vs r=0.45;p=0.01 vs r=-0.15;p=0.44). There is significant correlation between fat intake and sdLDL levels with r=0.45Conclusion: There was a significant correlation between fat intake and sdLDL levels in CHD patients. There is no significant correlation between refined and non-refined carbohydrates with sdLDL levels in CHD patients.